Technical potential of some Colombian cities for the development of grid connected PV systems through virtual instrumentation (2014)
This paper briefly describes the operation curves of some PV modules under actual irradiance conditions and temperature in 10 Colombian cities. Those curves were obtained from a Virtual Instrument (VI) developed in LabVIEW®. With the collected information from the VI, the cities were classified taking into account 5 parameters: solar irradiance, temperature, variability of solar resource, maximum power point and Photovoltaic (PV) modules efficiency in the cities. From the VI, an analytical methodology was developed to identify the technical potential of some regions for the implementation and development of grid connected PV systems. Additionally, users were able to get information on the solar irradiance potential, helping to achieve an accurate design of the PV systems.